Immoral geographies and Soho's sex shops: exploring spaces of sexual diversity in London. Issue 3 (4th March 2018) - Sanders-McDonagh, Erin; Peyrefitte, Magali
Abstract: London's Soho, situated in the urban heart of the city has long been understood as both a cosmopolitan and diverse space where transgression and deviance, particularly in relation to the sex industry and sexual commerce, are constitutive of this area. Drawing on three years of ethnographic fieldwork, we add to some of the existing debates on sexual spaces in Soho by documenting the changes to the social/sexual landscape of sex shops in this area, and look to geographers interested in the spatial politics of gender and sexuality to understand the importance of this particular place. Looking at two particular sex shops in Soho, we argue that the spatial practices in this very specific part of the city encourage a disruption of traditional hierarchies that often govern gender and sexed practices, and invite women, LGBTQ and kink communities to inhabit more inclusive spaces of sexual citizenship.